1999
DOI: 10.2307/2997958
|View full text |Cite
|
Sign up to set email alerts
|

By passing the Security Council: Ambiguous Authorizations to Use Force, Cease-Fires and the Iraqi Inspection Regime

Abstract: In January and February 1998, various United States officials, including the President, asserted that unless Iraq permitted unconditional access to international weapons inspections, it would face a military attack. The attack was not to be, in Secretary of State Madeleine Albright’s words, “a pinprick,” but a “significant” military campaign. U.S. officials, citing United Nations Security Council resolutions, insisted that the United States had the authority for the contemplated attack. Representatives of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…For examples on the pro-war side, see Brown (2003) and Condron (1999). For examples on the anti-war side, see Lobel & Ratner (1999) and White & Cryer (1999). 8.…”
Section: Discussionmentioning
confidence: 98%
“…For examples on the pro-war side, see Brown (2003) and Condron (1999). For examples on the anti-war side, see Lobel & Ratner (1999) and White & Cryer (1999). 8.…”
Section: Discussionmentioning
confidence: 98%
“…152 Often the act of stepping out of the Council yields complementary action, but sometimes, as in the extreme examples of Operation Allied Force or Operation Iraqi Freedom, it is a way of bypassing the Security Council. 153 In any case, the tactic of stepping outside the Council was already being questioned in the early 1990s, when Secretary General Boutros Boutros-Ghali warned that although such groups can make valuable contributions, they lead to confused lines of responsibility and effort. 154 Although by no means all the states involved in Groups of Friends are from the global Norththe Core Group for Haiti includes Latin American states like Brazil, and the Group of Friends for Libya includes a number states in the Middle East -it has been suggested that the tactic of leaving the Council to gain influence is limited to the richest, biggest, and best connected states.…”
Section: Transformation and Renewalmentioning
confidence: 99%
“…On this view, Resolution 678 becomes a "loaded weapon in the hands of any member state to use whenever it determined Iraq to be in material breach of the ceasefire." 50 In light of the objectives of minimizing the use of force and settling disputes by peaceful means that are central to the Charter framework, it is inappropriate to interpret the resolution in a manner that presumes that the Security Council has authorized the greatest amount of violence that the language could imply. More decisively, such an interpretation finds no support in the statements of the nations that voted for Resolution 678 or in subsequent debates in the Security Council.…”
Section: The Gentle Civilizer Of Nationsmentioning
confidence: 99%